Development of a Cyber Range with description language for network topology definition - Dalla Costa, Andrea (My University, 2023)
Cyber Ranges are an essential tool for cybersecurity trainings and experiments because they enable to setup virtual, isolated and reproducible environments that can be safely used to execute different types of tests and scenarios. The preparation of scenarios is the most time-consuming phase, which includes the configuration of the virtual machines and the definition of the network topology, so it is important for a Cyber Range to include tools that simplify this operation. This work focuses on how to implement and setup a Cyber Range that includes the necessary features and tools to simplify the setup phase, in particular for large topologies. The literature review provides an analysis of the selected open-source and research solutions currently available for Cyber Ranges and their configuration for use in different scenarios. This work presents the development of a Cyber Range based on the open-source framework OpenStack and the entire design process of a new Description Language, starting from the analysis of the requirements for the defined use-cases, defining and designing the required features, the implementation of all the required components, and the testing of the correctness and effectiveness of the whole system. A comparison of the implemented solution against the selected solutions in the literature study is provided, summarising the unique features offered by this approach. The validation of the Description Language implementation with the defined use cases demonstrated that it can reduce the complexity and length of the required template, which can help to make the setup of scenarios faster.